A Design of Plastic Melting Equipment Waste Bank Scale Using Quality Function Deployment Method: Studi kasus di bank sampah Gurami Semanu - Isana Arum Primasari; Endah Utami; Gita Indah Budiarti; Okka Adiyanto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The COVID-19 pandemic has triggered the rise of online purchases, resulting in the accumulation of plastic packaging waste. Plastic is most widely used because it is lightweight, flexible, cheap and easy to obtain, but its waste is difficult to decompose, which has an impact on the environment. Eco-bricking is one way that waste banks often reduce the amount of plastic waste. The obstacle in making eco-bricks is sore hands and calluses because it takes a lot of energy to compact the plastic. On the other hand, there is a lot of concentrated cooking oil waste that is still untreated, causing difficulties when disposing of it. Through this research, the design of a waste bank scale plastic melting machine is carried out with the raw materials of plastic bags and concentrated cooking oil into new materials that are more useful. The Quality Function Deployment (QFD) method with an Ergonomics approach is the basis for the stages of making product design from collecting consumer voices to making detailed tool designs. The operation of the tool uses simple technology so that it is easy to use by members of the Gurami Semanu waste bank. A total of 34 respondents will be the basis for determining product design. The results of the design of a bank-scale plastic melting tool in the form of a lidded stainless steel pot with a stirrer. The heater used for melting uses LPG gas with automatic operation using a button.